Studi Kelayakan Bisnis Pengembangan Usaha Aksesoris Jendela dan Pintu dalam Menghadapi Trend Pasar Industri Konstruksi (Studi Kasus CV. Subur Indah Pertama) - Erni Kasi Awa; Ni Luh Indiani; I Kadek Widhiantara (PT. PENERBIT TIGA MUTIARA, 2025)
This study aims to analyze the feasibility of business development for CV. Subur Indah Pertama, located in Pemecutan Kaja Village, North Denpasar, Bali, based on five main aspects of business feasibility studies: market and marketing, legal, human resources, environmental, and financial. This research employs a qualitative approach using descriptive methods, with data collection techniques including direct observation, in-depth interviews, and document review. The analysis results show that from the market and marketing aspect, the company has demonstrated positive performance through the optimization of digital platforms such as Tokopedia, Shopee, and TikTok, as well as strategic partnerships with contractors and property developers. Legally, the company is deemed feasible as it has fulfilled all business documents and licenses, including SIUP, NPWP, PKP, and tax compliance. In terms of human resources, a systematic organizational structure and professionally-based HR management indicate the company’s readiness to support business expansion. The environmental aspect also meets feasibility criteria, with evidence of standardized waste management systems and compliance with environmental regulations. From the financial perspective, the project is considered highly feasible based on financial indicators, namely a Net Present Value (NPV) of IDR 13.7 billion, an Internal Rate of Return (IRR) of 32%, and a Payback Period of 5 years, which is below the project’s economic life of 8 years. The IFAS and EFAS analyses show significant internal strengths, while the SWOT matrix places the company in Quadrant I with an aggressive strategy (Strength–Opportunity). Based on the overall findings, the business development of CV. Subur Indah Pertama is declared feasible and has strong prospects for long-term growth.